THE CRITIQUE OF ALTERNATIVE DISPUTE RESOLUTION UNDER ISLAMIC LAW AND ITS RELEVANCE IN THE CONTEMPORARY NIGERIA - Shittu-Adenuga , Zaynab Omotoyosi; Abiola , Adekunle Saheed; Mustapha , Sunkanmi Sodiq (Jurnal Syariah, 2023)
The practice of Alternative Disputes Resolution (ADR) such as Tahkim (arbitration), Sulh (mediation), ombudsman (Muḥtasib), expert opinion (fatwa) and other ways of compromising disputes out of court is sanctioned under Islamic law. Muslims need to know the relevance of these ADR processes and their applicability in the settlement of disputes. This is based on the authority that Allah unequivocally stated that Sulh is the best (Qur’an al-Nisa’: 128). This article offers a critique of ADR processes under Islamic law and the chances of its assimilation in Nigeria. This paper argued that the ADR processes are very significant in the administration of justice. The setback is in its application in Nigeria despite the practice of Shariah in about twelve states in Northern Nigeria. It is opined that individuals, institutions and courts have not manifestly practised ADR processes. This paper adopted a combination of doctrinal, empirical, historical and analytical research methods. We consulted primary and secondary materials, coupled with the use of questionnaires. The paper employed explorative method of data analysis. This paper revealed that the current application of Islamic ADRs is informal and unpopular as it lacks statutory backing in Nigeria. People are desirous to embracing it, which will help improve the administration of justice through the decongestion of court cases. This paper concludes that Islamic ADRs are effective for access to justice in Islam. The paper therefore recommended amongst others that Sulh should be statutorily provided for in Nigeria and adequate Islamic legal training of those involved in the administration of justice should be conducted to avoid an improper practice that will undermine its positive impact on the administration of justice in Nigeria.